Soil Nitrate Nitrogen Content and Grain Yields of Organically Grown Cereals as Affected by a Strip Tillage and Forage Legume Intercropping - Aušra Arlauskienė; Viktorija Gecaitė; Monika Toleikienė; Lina Šarūnaitė; Žydrė Kadžiulienė (Plants, 2021)
Reducing tillage intensity and increasing crop diversity by including perennial legumes is an agrotechnical practice that strongly affects the soil environment. Strip tillage may be beneficial in the forage legume–cereals intercropping system due to more efficient utilization of biological nitrogen. Field experiments were conducted on a clay loam Cambisol to determine the effect of forage legume–winter wheat strip tillage intercropping on soil nitrate nitrogen (N-NO3) content and cereal productivity in various sequences of rotation in organic production systems. Forage legumes (Medicago lupulina L., Trifolium repens L., T. alexandrinum L.) grown in pure and forage legume–winter wheat (Triticum aestivum L.) strip tillage intercrops were studied. Conventional deep inversion tillage was compared to strip tillage. Nitrogen supply to winter wheat was assessed by the change in soil nitrate nitrogen content (N-NO3) and total N accumulation in yield (grain and straw). Conventional tillage was found to significantly increase N-NO3 content while cultivating winter wheat after forage legumes in late autumn (0–30 cm layer), after growth resumption in spring (30–60 cm), and in autumn after harvesting (30–60 cm). Soil N-NO3 content did not differ significantly between winter wheat strip sown in perennial legumes or oat stubble. Winter wheat grain yields increased with increasing N-NO3 content in soil. The grain yield was not significantly different when comparing winter wheat–forage legume strip intercropping (without mulching) to strip sowing in oat stubble. In forage legume–winter wheat strip intercropping, N release from legumes was weak and did not meet wheat nitrogen requirements.